Fixed point theory, variational analysis, and optimization - Al-Mezel, Saleh Abdullah R.; Al-Solamy, Falleh Rajallah M.; Ansari, Qamrul Hasan (CRC Press, Taylor & Francis Group, 2014)
Fixed Point Theory, Variational Analysis, and Optimization not only covers three vital branches of nonlinear analysis-fixed point theory, variational inequalities, and vector optimization-but also explains the connections between them, enabling the study of a general form of variational inequality problems related to the optimality conditions involving differentiable or directionally differentiable functions. This essential reference supplies both an introduction to the field and a guideline to the literature, progressing from basic concepts to the latest developments.